Sealant resin composition and use thereof

By using the composite materials of propylene α-olefin copyright and propylene polymer with specific proportions and properties, the problem of insufficient heat seal strength is solved, and the good heat seal strength and appearance retention of packaging materials in high temperature environments is achieved, and it is suitable for a variety of packaging materials.

JP2025017223APending Publication Date: 2025-02-05MITSUI CHEMICALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023120219
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

In the prior art, the heat seal strength is insufficient, the heat seal durability is poor, and the heat seal strength is insufficient during the secondary processing, which cannot meet the appearance maintenance and heat seal strength requirements in high temperature environments.

Method used

The composite material formed by using propylene α-olefin copolymer and propylene polymer with specific proportions and performance requirements is used to prepare packaging materials with excellent heat seal strength and appearance retention.

Benefits of technology

It realizes packaging materials with good heat seal strength and appearance retention in high temperature environments, and is suitable for a variety of packaging materials, including food, medicine, electronic components, lithium-ion battery packaging, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017223000001
    Figure 2025017223000001
  • Figure 2025017223000002
    Figure 2025017223000002
Patent Text Reader

Abstract

To provide a sealant resin composition capable of producing a sealant film with excellent whitening resistance during drawing, excellent heat seal strength, and, excellent stickiness resistance, appearance retention and heat seal strength even after heat treatment.SOLUTION: A sealant resin composition (X) containing a propylene-α-olefin copolymer (A) that meets the following requirements (a1) to (a4), and a propylene-based polymer (B) with a melting point of 110 to 170°C and an isotactic pentad fraction of 90% or more. (a1) The content of structural units (i) derived from propylene is 51 to 95 mol%, and the content of structural units (ii) derived from α-olefins with a carbon atom count of 2 to 20, excluding propylene, is 5 to 49 mol%. (a2) An elution peak is 10 to 55°C. (a3) A ratio of eluted components at -20°C or below is 80 mass% or less. (a4) The melting point is 50 to 100°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealant resin composition and uses thereof. More specifically, the present invention relates to a sealant resin composition containing a propylene-α-olefin copolymer and a propylene-based polymer and uses thereof. [Background technology]

[0002] α-olefin resins are widely used as resins constituting heat-sealable sealant resin compositions and sealant films. For example, as sealant films for packaging applications, compositions in which propylene copolymers are blended with ethylene copolymers and films using only ethylene copolymers are used. Patent Document 1 describes a laminate having excellent low-temperature heat sealability, which includes a sealant film containing a polypropylene resin, an ethylene-α-olefin random copolymer, and a 1-butene-α-olefin random copolymer. Patent Document 2 discloses an easy-to-open sealant film containing a copolymer of ethylene and an α-olefin having 4 to 10 carbon atoms, and polypropylene. However, there are problems in that the heat seal strength is insufficient depending on the application, and the resistance to whitening during stretching in secondary processing and the heat seal strength after heat treatment are insufficient. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 11-221884 [Patent Document 2] JP 2020-114908 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a sealant resin composition capable of producing a sealant film which has excellent whitening resistance during stretching, good heat seal strength, and also has good stickiness resistance, appearance retention and heat seal strength even after heat treatment. [Means for solving the problem]

[0005] The present invention relates to, for example, the following [1] to

[11] . [1] A propylene / α-olefin copolymer (A) that satisfies the following requirements (a1) to (a4); A propylene-based polymer (B) that satisfies the following requirements (b1) and (b2); The sealant resin composition (X) contains the above. (a1): When the total of the structural unit (i) derived from propylene and the structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms other than propylene is taken as 100 mol %, the content of the structural unit (i) is 51 to 95 mol %, and the content of the structural unit (ii) is 5 to 49 mol %. (a2): In crystallization elution fractional chromatography measurement, the elution peak is at 10 to 55°C. (a3): In crystallization elution fractional chromatography, the ratio of components eluted at -20°C or lower is 80 mass% or less. (a4): The melting point measured by a differential scanning calorimeter is 50 to 100°C. (b1): The melting point measured by a differential scanning calorimeter is 110 to 170°C. (b2): The isotactic pentad fraction is 90% or more.

[0006] [2] The propylene / α-olefin copolymer (A) is Propylene-ethylene copolymer (A1), Propylene-1-butene copolymer (A2), Propylene-1-octene copolymer (A3) and Propylene-Ethylene-1-Butene Copolymer (A4) The sealant resin composition (X) according to [1], which consists of one or more selected from the group consisting of:

[0007] [3] The sealant resin composition (X) according to [1] or [2], further comprising an ethylene-based polymer (C). [4] The sealant resin composition (X) according to any one of [1] to [3], comprising the propylene-α-olefin copolymer (A) in an amount of 1 to 50 mass%, the propylene polymer (B) in an amount of 30 to 99 mass%, and an ethylene polymer (C) in an amount of 0 to 20 mass% (wherein the total of the propylene-α-olefin copolymer (A), the propylene polymer (B), and the ethylene polymer (C) is taken as 100 mass%).

[0008] [5] A sealant film comprising at least one layer containing the sealant resin composition (X) according to any one of [1] to [4]. [6] A laminate comprising a sealant layer containing the sealant resin composition (X) according to any one of [1] to [4] and a base layer, wherein the base layer is made of at least one base film selected from the group consisting of a polyolefin film, a polystyrene film, a polyester film, a polyamide film, a laminate film of a polyolefin and a gas barrier resin film, a metal foil, paper, and a vapor-deposited film.

[0009] [7] The sealant layer and the base layer are bonded together by any one of a melt extrusion lamination method, a thermal lamination method, and a dry lamination method. The laminate described in [6]. [8] The laminate according to [6] or [7], wherein the base film is an aluminum foil.

[0010] [9] A package comprising the laminate according to any one of [6] to [8].

[10] A lithium ion battery comprising the packaging body according to [9].

[11] An electricity storage device comprising the sealant film according to [5]. Effect of the Invention

[0011] According to the present invention, a resin composition can be provided that can produce a film that includes a layer made of a resin composition and is suitable as a sealant film. A single-layer or multi-layer film that includes a layer formed from the resin composition of the present invention has excellent whitening resistance during stretching, good heat seal strength, and also has good stickiness resistance, appearance retention, and heat seal strength even after heat treatment, making it suitable as a sealant film, and can be suitably used as, for example, daily necessities, food, liquids, medicines, electronic parts, lithium ion battery packaging, building materials, exterior materials for electricity storage devices, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] <Sealant resin composition (X)> The sealant resin composition (X) of the present invention contains a propylene / α-olefin copolymer (A) and a propylene-based polymer (B).

[0013] · Propylene-α-olefin copolymer (A) The propylene / α-olefin copolymer (A) according to the present invention satisfies all of the following requirements (a1) to (a4): (a1): When the total of the structural unit (i) derived from propylene and the structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms other than propylene is taken as 100 mol %, the content of the structural unit (i) is 51 to 95 mol %, and the content of the structural unit (ii) is 5 to 49 mol %. (a2): In crystallization elution fractional chromatography measurement, the elution peak is at 10 to 55°C. (a3): In crystallization elution fractional chromatography, the ratio of components eluted at -20°C or lower is 80 mass% or less. (a4): The melting point measured by a differential scanning calorimeter is 50 to 100°C.

[0014] Each of these requirements is discussed in more detail below. [Requirement (a1)] (a1): When the total of the structural unit (i) derived from propylene and the structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms other than propylene is taken as 100 mol %, the content of the structural unit (i) is 51 to 95 mol %, and the content of the structural unit (ii) is 5 to 49 mol %. The propylene-α-olefin copolymer (A) according to the present invention preferably has a content of the structural unit (i) of 55 to 94 mol % and a content of the structural unit (ii) of 6 to 45 mol %, and more preferably has a content of the structural unit (i) of 58 to 93 mol % and a content of the structural unit (ii) of 7 to 42 mol %.

[0015] The propylene-α-olefin copolymer (A) according to the present invention can have good compatibility with the propylene polymer (B) described below by setting the contents of the structural unit (i) and the structural unit (ii) within the above ranges. When the content of the structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms excluding propylene is equal to or less than the above upper limit, the whitening resistance during stretching in secondary processing such as deep drawing is improved when used as a sealant, and when the content is equal to or more than the above lower limit, the heat seal strength and heat seal strength after heat treatment, and the appearance after storage at high temperature are excellent, which is preferable.

[0016] Examples of the α-olefins from which the structural unit (ii) of the propylene-α-olefin copolymer (A) is derived include linear α-olefins such as ethylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, as well as branched α-olefins such as 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3-ethyl-1-pentene, 4,4-dimethyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4-ethyl-1-hexene, and 3-ethyl-1-hexene. Among these, α-olefins having 2 to 10 carbon atoms excluding propylene are preferred, α-olefins having 2 to 8 carbon atoms excluding propylene are more preferred, and ethylene and 1-butene are even more preferred. The structural unit (ii) may be derived from one of these compounds or from two or more of these compounds.

[0017] The propylene / α-olefin copolymer (A) is not particularly limited as long as the contents of the structural units (i) and (ii) are within the above-mentioned ranges. Preferred examples include, for example, a propylene / ethylene copolymer (A1), a propylene / 1-butene copolymer (A2), a propylene / 1-octene copolymer (A3), and a propylene / ethylene / 1-butene copolymer (A4). In a preferred embodiment of the present invention, the propylene / α-olefin copolymer (A) contains one or more of these (A1) to (A4). In a more preferred embodiment of the present invention, the propylene / α-olefin copolymer (A) consists of one or more of these (A1) to (A4).

[0018] The propylene-ethylene copolymer (A1) is a copolymer in which the structural unit (ii) is derived from ethylene, and the contents of the structural units (i) and (ii) are preferably such that the content of the structural unit (i) is 70 to 94 mol % and the content of the structural unit (ii) is 6 to 30 mol %, and more preferably the content of the structural unit (i) is 80 to 93.5 mol % and the content of the structural unit (ii) is 6.5 to 20 mol %.

[0019] The propylene-1-butene copolymer (A2) is a copolymer in which the structural unit (ii) is derived from 1-butene, and the contents of the structural units (i) and (ii) are preferably such that the content of the structural unit (i) is 65 to 92 mol % and the content of the structural unit (ii) is 8 to 35 mol %, and more preferably the content of the structural unit (i) is 70 to 88 mol % and the content of the structural unit (ii) is 12 to 30 mol %. The propylene-1-octene copolymer (A3) is a copolymer in which the structural unit (ii) is a structural unit derived from 1-octene, and the contents of the structural units (i) and (ii) are preferably such that the content of the structural unit (i) is 70 to 94 mol % and the content of the structural unit (ii) is 6 to 30 mol %, and more preferably the content of the structural unit (i) is 80 to 93.5 mol % and the content of the structural unit (ii) is 6.5 to 20 mol %.

[0020] The propylene-ethylene-1-butene copolymer (A4) is a copolymer in which the structural unit (ii) is composed of a structural unit (ii-1) derived from ethylene and a structural unit (ii-2) derived from 1-butene, and the contents of the structural unit (i), the structural unit (ii-1) derived from ethylene and the structural unit (ii-2) derived from 1-butene (wherein the total amount of the structural units (i), the structural units (ii-1) and the structural units (ii-2) is 100 mol %) are preferably such that the content of the structural unit (i) is 60 to 90 mol %, the content of the structural unit (ii-1) is 4 to 20 mol % and the content of the structural unit (ii-2) is 6 to 27 mol %, and more preferably the content of the structural unit (i) is 62 to 86 mol %, the content of the structural unit (ii-1) is 6 to 15 mol %, and the content of the structural unit (ii-2) is 8 to 23 mol %.

[0021] The monomers (propylene, α-olefin, etc.) constituting the propylene-α-olefin copolymer (A) may be derived from biomass or fossil fuel, or both of them may be used.

[0022] [Requirement (a2)] (a2): In crystallization elution fractional chromatography measurement, the elution peak is at 10 to 55°C. The propylene / α-olefin copolymer (A) according to the present invention has an elution peak of 10 to 55°C, preferably 13 to 54°C, more preferably 16 to 53°C, and even more preferably 18 to 52°C, as measured by crystallization elution fractional chromatography (CEF).

[0023] Crystallization elution fractionation chromatography (CEF) measurement was performed by the method described in the Examples below. The temperature at the apex of the elution peak was taken as the elution peak temperature, and the peak area was calculated from the integrated value of the peak, and the proportion of the component eluted at -20°C was calculated as the amount of the component eluted at -20°C. By setting the elution peak of the propylene-α-olefin copolymer (A) to the lower limit or higher, the stickiness resistance, appearance retention and heat seal strength after heat treatment at high temperatures (e.g. 80°C or higher) are improved, which is preferable. By setting the elution peak to the upper limit or lower, the whitening resistance is excellent, which is preferable.

[0024] [Requirement (a3)] (a3): In crystallization elution fractional chromatography, the ratio of components eluted at -20°C or lower is 80 mass% or less. The propylene-α-olefin copolymer (A) according to the present invention has a ratio of components eluted at -20°C or lower, as measured by crystallization elution fractional chromatography (CEF), of 80% by mass or less, preferably 0.1 to 50% by mass, more preferably 0.2 to 10% by mass, and even more preferably 0.3 to 5% by mass. The components of propylene-α-olefin copolymer (A) that leach below -20°C are usually amorphous components, and if contained in excess, they may bleed out to the surface after heat treatment and become a factor in impairing heat sealability. It is preferable to keep the ratio of components that leach below -20°C of propylene-α-olefin copolymer (A) below the upper limit value, as this increases the heat seal strength after heat treatment.

[0025] [Requirements (a4)] (a4): The melting point measured by a differential scanning calorimeter is 50 to 100°C. The propylene / α-olefin copolymer (A) according to the present invention has a melting point measured by a differential scanning calorimeter of 50 to 100°C, preferably 55 to 99°C. The melting point of the propylene / α-olefin copolymer (A) is preferably equal to or higher than the lower limit, since it provides high stickiness resistance, appearance retention and heat seal strength after heat treatment at high temperatures (e.g., 80°C or higher). The melting point is preferably equal to or lower than the upper limit, since it provides excellent whitening resistance. The melting point can be measured by a method described in the Examples below using a differential scanning calorimeter. Here, the melting point refers to the temperature at the peak of the heat of fusion. When two or more melting peaks are observed, the lowest temperature among the temperatures at the peaks of these peaks is the melting point.

[0026] The propylene / α-olefin copolymer (A) according to the present invention preferably satisfies one or more of the following requirements (a5) to (a10), in addition to the above requirements (a1) to (a4), more preferably satisfies two or more of the following requirements (a5) to (a10), and particularly preferably satisfies all of the following requirements:

[0027] [Requirement (a5)] (a5): The heat of fusion measured by a differential scanning calorimeter is 10 to 50 J / g. The propylene / α-olefin copolymer (A) according to the present invention preferably has a heat of fusion measured by a differential scanning calorimeter of 10 to 50 J / g, more preferably 15 to 48 J / g. The propylene-α-olefin copolymer (A) is preferably provided with a heat of fusion equal to or higher than the lower limit, since this improves the stickiness resistance, appearance retention and heat seal strength after heat treatment at high temperatures (e.g., 80°C or higher). Also, the propylene-α-olefin copolymer (A) is preferably provided with a heat of fusion equal to or lower than the upper limit, since this improves the whitening resistance. The heat of fusion can be measured using a differential scanning calorimeter by the method described in the Examples below.

[0028] [Requirement(a6)] (a6): The B value calculated by the following formula (1) is 0.9 to 1.5. B=M OE / (2M O ×M E ) ····(1) (In formula (1), M OE represents the molar fraction of the chains of propylene and ethylene and the chains of α-olefins having 4 to 20 carbon atoms and ethylene relative to the total number of dyads, and M O represents the sum of the mole fractions of propylene and α-olefins having 4 to 20 carbon atoms, and M Erepresents the mole fraction of ethylene.)

[0029] When the propylene / α-olefin copolymer (A) according to the present invention is a propylene / ethylene copolymer (A1), the above-mentioned B value is preferably 0.9 to 1.5, more preferably 0.9 to 1.2. It is preferable for the B value to be within the above range since the compatibility with the propylene polymer (B) is excellent and the whitening resistance is excellent.

[0030] The larger the B value, the shorter the block chain of ethylene units and the more uniform the distribution of ethylene units. Conversely, the smaller the B value, the less uniform the distribution of ethylene units and the longer the block chain. The B value can be determined by the method described in JP-A-2007-186664.

[0031] [Requirement (a7)] (a7): The mm fraction is 80% or more. The propylene / α-olefin copolymer (A) according to the present invention preferably has an mm fraction of 80% or more, more preferably 85 to 98%, and even more preferably 87 to 95%.

[0032] Here, the mm fraction means the isotactic triad fraction measured by the NMR method. The mm fraction (isotactic triad fraction) is 13 It indicates the proportion of isotactic sequences in triad units in a molecular chain measured using C-NMR, and is the fraction of propylene monomer units at the center of a chain in which three consecutive propylene monomer units are meso-bonded. Specifically, 13 It is a value calculated as the fraction of mm peaks in the total absorption peaks in the methyl carbon region observed in the C-NMR spectrum. The isotactic triad fraction (mm fraction) is 13 Pmm (absorption intensity due to the methyl group of the second unit at the site where three consecutive propylene units are isotactically bonded) and PW It is calculated from the absorption intensity (absorption intensity due to all methyl groups of the propylene unit) using the following formula. mm fraction=Pmm / P W

[0033] The mm fraction can be measured and analyzed by the method described in JP-A-2007-186664. When the mm fraction is within the above range, the propylene / α-olefin copolymer (A) according to the present invention has a substantially isotactic structure. The sealant resin composition (X) containing the propylene-α-olefin copolymer (A) having a mm fraction within the above range is preferable because it has excellent mechanical strength and heat seal strength, and is also preferable because it has high stickiness resistance, appearance retention, and heat seal strength after heat treatment at high temperatures (e.g., 80°C or higher).

[0034] [Requirement (a8)] (a8): The melt flow rate (MFR) measured according to ASTM D1238 at 230° C. under a load of 2.16 kg is 0.1 to 50 g / 10 min. The propylene / α-olefin copolymer (A) according to the present invention has an MFR (230° C., 2.16 kg load) of preferably 0.1 to 50 g / 10 min, more preferably 0.5 to 20 g / 10 min, and further preferably 1 to 13 g / 10 min.

[0035] When the MFR of the propylene-α-olefin copolymer (A) is equal to or higher than the lower limit, the drawdown property is good when forming a film from the sealant resin composition (X) containing the copolymer, and the composition is suitable for high-speed film formation. When the MFR is equal to or lower than the upper limit, the composition has excellent mechanical strength and heat seal strength. In addition, the composition is suitable for high stickiness resistance, appearance retention, and heat seal strength after heat treatment at high temperatures (e.g., 80°C or higher).

[0036] [Requirement(a9)] (a9): The weight average molecular weight (Mw) is 100,000 to 10,000,000. The propylene / α-olefin copolymer (A) according to the present invention has a weight average molecular weight (Mw) of preferably 100,000 to 10,000,000, more preferably 120,000 to 1,000,000, and even more preferably 150,000 to 500,000. The weight average molecular weight (Mw) can be measured by GPC (gel permeation chromatography) and calculated in terms of polystyrene. When the Mw of the propylene-α-olefin copolymer (A) is equal to or higher than the upper limit, the drawdown property is good when the sealant resin composition (X) containing the copolymer is molded into a film, and the film is suitable for high-speed film formation. When the Mw is equal to or lower than the lower limit, the mechanical strength and heat seal strength are excellent. In addition, the stickiness resistance after heat treatment at high temperatures (e.g., 80°C or higher), the appearance retention, and the heat seal strength after heat treatment are high, which is preferable.

[0037] [Requirement (a10)] (a10): The molecular weight distribution (Mw / Mn) is 3.5 or less. The propylene / α-olefin copolymer (A) according to the present invention has a molecular weight distribution (Mw / Mn) of preferably 3.5 or less, more preferably 1.5 to 3.0, and even more preferably 1.8 to 2.5. The molecular weight distribution (Mw / Mn) is a value determined from the ratio of the weight average molecular weight (Mw) and the number average molecular weight (Mn) measured by GPC and calculated in terms of polystyrene. When the Mw / Mn of the propylene-α-olefin copolymer (A) is within the above range, when the sealant resin composition (X) containing the copolymer is molded into a film, the film has excellent stickiness resistance after heat treatment at high temperatures (e.g., 80°C or higher), which is preferable.

[0038] · Propylene polymer (B) The propylene polymer (B) according to the present invention satisfies the following requirements (b1) and (b2). The propylene polymer (B), which is one of the components of the sealant resin composition (X) of the present invention, may be a polymer or copolymer in which a structural unit derived from propylene is the main structural unit, and is not particularly limited as long as it satisfies the following requirements (b1) and (b2).

[0039] The propylene polymer (B) preferably contains 51 to 100 mol % of structural units derived from propylene, and may be, for example, a homopolypropylene, a copolymer of propylene and an α-olefin having 2 to 20 carbon atoms other than propylene (random polypropylene), or a block copolymer, with random polypropylene being preferred.

[0040] The monomers (propylene, α-olefin, etc.) contained in the propylene-based polymer (B) may be derived from biomass or fossil fuel, or both of the biomass-derived monomers and the fossil fuel-derived monomers may be used.

[0041] [Requirement (b1)] (b1): The melting point measured by a differential scanning calorimeter is 110 to 170°C. The propylene polymer (B) according to the present invention has a melting point of 110 to 170°C, preferably 130 to 160°C, as measured by a differential scanning calorimeter. A sealant resin composition (X) containing a propylene polymer (B) having a melting point within the above range has an excellent balance between flexibility and heat resistance. A sealant resin composition (X) containing a propylene polymer (B) having a melting point equal to or lower than the upper limit has excellent flexibility and whitening resistance. A sealant resin composition containing a propylene polymer (B) having a melting point equal to or higher than the lower limit has excellent stickiness resistance, appearance retention, and heat seal strength after heat treatment at high temperatures (e.g., 80°C or higher).

[0042] [Requirement (b2)] (b2): The isotactic pentad fraction is 90% or more. The propylene polymer (B) according to the present invention has an isotactic pentad fraction (mmmm fraction) of 90% or more, preferably 92% or more, more preferably 95% or more. Such a propylene polymer (B) is a substantially isotactic propylene polymer.

[0043] The isotactic pentad fraction (mmmm fraction) is 13 It indicates the proportion of isotactic chains in pentad units in a molecular chain measured using C-NMR, and is the fraction of propylene monomer units at the center of a chain in which five consecutive propylene monomer units are meso-bonded. Specifically, 13 It is a value calculated as the fraction of mmmm peaks in the total absorption peaks in the methyl carbon region observed in a C-NMR spectrum. This isotactic pentad fraction (mmmm fraction) is, for example, as described in JP 2007-186664 A, 13 This is the proportion of isotactic chains in pentad units in a molecular chain measured using C-NMR, in other words, the fraction of propylene monomer units at the center of a chain in which five consecutive propylene monomer units are meso-bonded, and can be measured by the method described in the publication.

[0044] When the isotactic pentad fraction (mmmm fraction) is within the above range, a molded product can be easily obtained that has an excellent balance between flexibility and heat resistance, and is particularly excellent in whitening resistance, heat seal strength, stickiness resistance after heat treatment at high temperatures (e.g., 80°C or higher), appearance retention, and heat seal strength after heat treatment.

[0045] The propylene polymer (B) according to the present invention preferably satisfies the following requirement (b3) in addition to the requirements (b1) and (b2).

[0046] [Requirement (b3)] (b3): ​​The melt flow rate (MFR) measured according to ASTM D1238 at 230° C. under a load of 2.16 kg is 0.1 to 50 g / 10 min. The propylene polymer (B) according to the present invention has an MFR (230°C, 2.16 kg load) of preferably 0.1 to 50 g / 10 min, more preferably 0.5 to 20 g / 10 min, and even more preferably 1 to 13 g / 10 min. When the MFR of the propylene polymer (B) is equal to or higher than the lower limit, the drawdown property is good when the sealant resin composition (X) containing the polymer is molded into a film, and the film is suitable for high-speed film formation. When the MFR is equal to or lower than the upper limit, the mechanical strength and heat seal strength are excellent.

[0047] Other Ingredients The sealant resin composition (X) of the present invention may contain, in addition to the above-mentioned propylene-α-olefin copolymer (A) and propylene-based polymer (B), other components within the scope of the present invention, for example, resin components, additives, etc. other than the propylene-α-olefin copolymer (A) and the propylene-based polymer (B).

[0048] The resin component other than the propylene-α-olefin copolymer (A) and the propylene-based polymer (B) is not particularly limited, but a preferred example is an ethylene-based polymer (C).

[0049] · Ethylene polymer (C) The sealant resin composition (X) of the present invention may further contain an ethylene-based polymer (C). The ethylene-based polymer (C) may be a polymer or copolymer in which the main constituent unit is a constituent unit derived from ethylene, and preferably contains 60 to 100 mol % of the constituent unit derived from ethylene. Specific examples of the ethylene-based polymer (C) according to the present invention include high-pressure low-density polyethylene (C1) and ethylene-α-olefin copolymer (C2).

[0050] The monomers (ethylene, α-olefin, etc.) contained in the ethylene polymer (C) may be derived from biomass or fossil fuel, and both of the biomass-derived monomers and the fossil fuel-derived monomers may be used.

[0051] By using the ethylene polymer (C), the resulting sealant resin composition (X) is particularly excellent in high-speed film-forming property, and a molded article having a well-balanced excellent impact resistance and heat seal strength can be easily obtained.

[0052] <High-pressure low-density polyethylene (C1)> Any known high-pressure low-density polyethylene can be used without restriction as the high-pressure low-density polyethylene (C1). The high-pressure low-density polyethylene is generally obtained by radical polymerization of ethylene under high temperature and high pressure, and the method for producing it is not particularly limited, but includes, for example, a radical polymerization method in which radical polymerization is performed under conditions of 500 to 2000 atmospheric pressure and 150 to 300°C, and the polymerization initiator here includes, for example, an organic peroxide.

[0053] High-pressure low-density polyethylene (C1) has a density of 900 to 925 kg / m3 as measured in accordance with ASTM D1505. 3 and more preferably in the range of 910 to 925 kg / m 3 It is.

[0054] The high-pressure low-density polyethylene (C1) preferably has a melt flow rate (MFR) measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg of 0.1 to 50 g / 10 min, more preferably 0.5 to 30 g / 10 min, and even more preferably 1 to 20 g / 10 min.

[0055] Ethylene-α-olefin copolymer (C2) The ethylene-α-olefin copolymer (C2) contains at least constitutional units derived from ethylene and constitutional units derived from an α-olefin having 3 to 20 carbon atoms.

[0056] The content of structural units derived from ethylene in the ethylene-α-olefin copolymer (C2) is preferably 60 to 99 mol %, more preferably 65 to 99 mol %, further preferably 70 to 99 mol %, and particularly preferably 80 to 99 mol %.

[0057] Ethylene-α-olefin copolymer (C2) is characterized by having fewer long-chain branched structures compared to high-pressure low-density polyethylene (C1), and is generally referred to as linear low-density polyethylene (LLDPE).

[0058] The content of structural units derived from an α-olefin having 3 to 20 carbon atoms in the ethylene-α-olefin copolymer (C2) is preferably 1 to 40 mol %, more preferably 1 to 35 mol %, even more preferably 1 to 30 mol %, and particularly preferably 1 to 20 mol %.

[0059] These contents are based on 100 mol % in total of the structural units derived from ethylene and the α-olefin having 3 to 20 carbon atoms. When the content of the structural units is within the above range, a molded article having a good balance between impact resistance and flexibility can be easily obtained.

[0060] Examples of the α-olefin having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-nonadecene, and 1-eicosene. Among these, α-olefins having 3 to 10 carbon atoms are preferred, α-olefins having 3 to 8 carbon atoms are more preferred, propylene, 1-butene, and 1-octene are even more preferred, and propylene is particularly preferred. The α-olefins having 3 to 20 carbon atoms may be used alone or in combination of two or more kinds.

[0061] Specific examples of the ethylene-α-olefin copolymer (C2) include ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-1-butene-1-octene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-hexene copolymer, and ethylene-1-octene copolymer. Among these, for example, ethylene-propylene copolymer and ethylene-1-butene copolymer are preferred.

[0062] The density of ethylene-α-olefin copolymer (C2) is 850-890kg / m 3 is preferably 860 to 880 kg / m 3 It is more preferable that:

[0063] When the density is within the above range, a molded article having a good balance between impact resistance and heat seal strength can be easily obtained. The density can be measured by a density gradient tube method.

[0064] The MFR of the ethylene-α-olefin copolymer (C2) (measured in accordance with ASTM D1238 at 190°C under a load of 2.16 kg) is preferably 0.01 to 40 g / 10 min, more preferably 0.1 to 20 g / 10 min, and still more preferably 0.3 to 10 g / 10 min.

[0065] When the MFR is within the above range, a molded article having excellent and well-balanced impact resistance and heat seal strength can be easily obtained.

[0066] The ethylene-α-olefin copolymer (C2) can be produced by a conventional method using a vanadium catalyst, a titanium catalyst, a metallocene catalyst, etc. Preferably, a metallocene catalyst is used for production, which allows a copolymer having a narrow molecular weight distribution and composition distribution to be obtained, and is more preferable in terms of mechanical properties, transparency, and impact resistance.

[0067] Additives The sealant resin composition (X) of the present invention may contain additives such as weathering stabilizers, heat stabilizers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, nucleating agents, lubricants, pigments, dyes, plasticizers, antioxidants, hydrochloric acid absorbers, antioxidants, etc., as necessary, within the scope of the present invention. The amount of these additives is not particularly limited, but it is desirable that the total amount of the additives is usually 10 parts by mass or less, preferably 5 parts by mass or less, more preferably in the range of 0.1 to 3 parts by mass, per 100 parts by mass of the resin components in the sealant resin composition (X) (the total of the propylene-α-olefin copolymer (A) and the propylene-based polymer (B) and other resin components such as the ethylene-based polymer (C)).

[0068] ·Sealant resin composition The sealant resin composition (X) of the present invention is a composition containing the above-mentioned propylene / α-olefin copolymer (A), the above-mentioned propylene-based polymer (B), and, if necessary, other components such as the above-mentioned ethylene-based polymer (C).

[0069] The sealant resin composition (X) may be A composition comprising a propylene / α-olefin copolymer (A) and a propylene-based polymer (B); A composition comprising a propylene-α-olefin copolymer (A), a propylene-based polymer (B) and a high-pressure low-density polyethylene (C1); A composition comprising a propylene / α-olefin copolymer (A), a propylene-based polymer (B) and an ethylene / α-olefin copolymer (C2), and A composition comprising a propylene / α-olefin copolymer (A), a propylene-based polymer (B), a high-pressure low-density polyethylene (C1), and an ethylene / α-olefin copolymer (C2). Examples include:

[0070] The sealant resin composition (X) preferably satisfies the requirement (X1). [Requirements (X1)] (X1): The content of the propylene-α-olefin copolymer (A) is in the range of 1 to 50 mass%, the content of the propylene-based polymer (B) is in the range of 30 to 99 mass%, and the content of the ethylene-based polymer (C) is in the range of 0 to 20 mass% (wherein the total of the propylene-α-olefin copolymer (A), the propylene-based polymer (B), and the ethylene-based polymer (C) is 100 mass%).

[0071] Preferably, the sealant resin composition (X) has a propylene-α-olefin copolymer (A) content in the range of 1 to 40 mass%, a propylene polymer (B) content in the range of 42 to 99 mass%, and an ethylene polymer (C) content in the range of 0 to 18 mass% (wherein the total of the propylene-α-olefin copolymer (A), the propylene polymer (B), and the ethylene polymer (C) is 100 mass%).

[0072] When the content of the propylene-α-olefin copolymer (A) is less than the upper limit, the film has excellent whitening resistance, and when it is more than the lower limit, the film has excellent stickiness resistance after heat treatment at high temperatures (e.g., 80°C or higher), appearance retention, and heat seal strength after heat treatment. When the content of the propylene polymer (B) is equal to or more than the lower limit, the film has excellent whitening resistance, and when the content is equal to or less than the upper limit, the film has excellent stickiness resistance, appearance retention, and heat seal strength after heat treatment at high temperatures (e.g., 80°C or higher). When the content of the ethylene polymer (C) is within the above range, the film is excellent in high-speed film-forming property and in heat seal strength.

[0073] Method for producing sealant resin composition (X) The sealant resin composition (X) of the present invention can be prepared by mixing the propylene / α-olefin copolymer (A) and the propylene-based polymer (B), as well as any optional components, as required, by a conventionally known method.

[0074] The method for producing the sealant resin composition (X) of the present invention is not particularly limited, but for example, the above propylene-α-olefin copolymer (A) and propylene polymer (B), and if necessary, ethylene polymer (C), and if necessary, other optional components, can be mixed in a predetermined mixing ratio, for example, with a Henschel mixer, V-blender, ribbon blender, tumbler blender, kneader-ruder, etc., or, after mixing or without mixing, melt-kneading with a single-screw extruder, twin-screw extruder, kneader, Banbury mixer, etc. Furthermore, granulation, pulverization, etc. may be carried out as necessary. When mixing or kneading these components, each component may be added at once or in stages.

[0075] The method of melt kneading is not particularly limited, and can be carried out using a melt kneading device such as a commercially available extruder. For example, the temperature of the part where kneading is carried out in the melt kneading device is usually 170 to 250° C., preferably 190 to 230° C. The kneading time is usually 0.5 to 30 minutes, particularly preferably 0.5 to 5 minutes.

[0076] <Sealant films and laminates> The sealant film according to the present invention is a single-layer or multi-layer sealant film containing at least one layer containing the above-mentioned sealant resin composition (X) of the present invention. In the present invention, the term "film" includes film-like objects and sheet-like objects. The sealant film having a layer containing the sealant resin composition (X) can be produced using a conventionally known single-layer or multi-layer film forming machine. The sealant film of the present invention may be a single layer film consisting of only a layer containing the sealant resin composition (X), may be a laminate having a plurality of layers containing the sealant resin composition (X), or may be a laminate containing a layer containing the sealant resin composition (X) and a substrate layer. That is, the sealant film of the present invention may be composed only of the above-mentioned sealant resin composition (X) of the present invention, or may be a laminate of a layer containing the sealant resin composition and a layer consisting of another substrate.

[0077] The laminate of the present invention is a laminate obtained by laminating a sealant layer containing the above-mentioned sealant resin composition (X) of the present invention and a substrate layer. Such a laminate can be suitably used as a sealant film.

[0078] The substrate layer constituting the laminate is not particularly limited, but is preferably a film-like or sheet-like substrate film. As the substrate film, for example, a single-layer or multi-layer resin film such as polyolefin resin (e.g., polyethylene, polypropylene), polyester resin, polycarbonate resin, polyarylate resin, acrylic resin, polyphenylene sulfide resin, polystyrene resin, vinyl resin, vinyl chloride resin, polyimide resin, epoxy resin, etc.; a film-like or sheet-like material such as paper, woven fabric, nonwoven fabric, metal foil, vapor deposition film, inorganic thin film, or a laminate thereof can be used, and these can be selected and used according to the purpose.

[0079] In the laminate of the present invention, the base layer is preferably at least one base film selected from the group consisting of a polyolefin film, a polystyrene film, a polyester film, a polyamide film, a laminate film of a polyolefin and a gas barrier resin film, a metal foil such as an aluminum foil or a copper foil, paper, and a vapor-deposited film. Such a laminate having a base layer and a sealant layer is easy to produce and has excellent handleability, and can be suitably used as a sealant film.

[0080] The laminate of the present invention may be produced by any method, and the production method is not limited thereto. However, it is preferable that the sealant layer and the base layer are bonded together by any one of a melt extrusion lamination method, a thermal lamination method, and a dry lamination method, since this method provides a laminate having excellent adhesion between the sealant layer and the base layer.

[0081] The sealant film or laminate containing the sealant resin composition (X) of the present invention may be either a stretched film or a non-stretched film, but is preferably a non-stretched film. The non-stretched film is not particularly limited as long as it is a non-stretched film, and the shape, size (thickness), etc. may be appropriately selected according to the desired application. The non-stretched film may be a single layer or a multilayer. When it is a multilayer, at least one of the layers may be a film containing the sealant resin composition (X) of the present invention. This includes a method of co-extrusion by a known multilayer film forming method such as a T-die film forming method or an inflation film forming method, and a method in which a layer containing the sealant resin composition (X) of the present invention is further laminated on a previously formed substrate. The substrate is not particularly limited, and may be a metal such as aluminum foil, steel foil, or stainless steel foil, or a thermoplastic resin. When the non-stretched film is a multilayer, it means that all layers are not stretched.

[0082] The thickness of the unstretched film (total thickness when it is a multilayer (laminate)) is preferably 5 μm or more, more preferably 10 μm or more, and is preferably 150 μm or less, more preferably 100 μm or less. In this specification, there is no particular distinction between a film and a sheet, but a film usually refers to a membranous body having a thickness of less than 250 μm, and a sheet usually refers to a thin plate-like body having a thickness of 250 μm or more. The sealant film of the present invention includes both film-like and sheet-like embodiments, and its thickness is not particularly limited, and is, for example, about 1 μm to 1000 μm, preferably 5 μm to 500 μm, and more preferably about 10 μm to 250 μm. When the sealant film is a multi-layer (laminate), it is desirable that the layer containing the sealant resin composition (X) is 1 μm or more, preferably 5 μm or more. When the film thickness is in this range, sufficient heat seal strength is obtained.

[0083] Applications of the sealant film and laminate of the present invention include, for example, packaging films for packaging food, liquids, medicines, electronic components, batteries, etc., and construction material films, packaging materials obtained therefrom, packaging bodies such as food packaging bodies, construction materials, and electricity storage devices.

[0084] <Application> The sealant film of the present invention and the laminate having a sealant layer and a substrate layer can be suitably used as a packaging film, a packaging material, a packaging body, a building material, and a film for a building material for packaging various items including daily necessities, foods, liquids, medicines, electronic parts, batteries, electricity storage devices, etc. by utilizing the properties of the sealant film. In addition, the sealant film can be suitably used as a packaging body for lithium ion batteries and an exterior material for electricity storage devices. EXAMPLES

[0085] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0086] The polymers and the like used in the examples and comparative examples are shown below. [Propylene-α-olefin copolymer (A)] The following propylene-α-olefin copolymers (A) (A1-1) to (A1-4) and (A2-1) to (A2-2) were used. (A1-1): Propylene-ethylene copolymer (ethylene content: 12.7 mol%, MFR (230°C, 2.16 kg load): 8 g / 10 min, melting point: 80°C, heat of fusion: 32 J / g, mm fraction: 90%) (A1-2): Propylene-ethylene copolymer (ethylene content: 16.2 mol%, MFR (230°C, 2.16 kg load): 8 g / 10 min, melting point: 57°C, heat of fusion: 26.2 J / g, mm fraction: 89%) (A1-3): Propylene-ethylene copolymer (ethylene content: 6.7 mol%, MFR (230°C, 2.16 kg load): 8 g / 10 min, melting point: 105°C, heat of fusion: 54 J / g, mm fraction: 89%) (A1-4): Propylene-ethylene copolymer (ethylene content 21.4 mol%, MFR (230°C, 2.16 kg load): 3 g / 10 min, melting point: 44°C, heat of fusion: 2.9 J / gJ / g, mm fraction: 89%)

[0087] (A2-1): Propylene-1-butene copolymer (1-butene content 26.0 mol%, MFR (230°C, 2.16 kg load): 7 g / 10 min, melting point: 79°C, heat of fusion: 39.4 J / g, mm fraction: 91%) (A2-2): Propylene-1-butene copolymer (1-butene content 16.0 mol%, MFR (230°C, 2.16 kg load): 7 g / 10 min, melting point: 98°C, heat of fusion: 46.9 J / g, mm fraction: 91%)

[0088] [Propylene-based polymer (B)] The following propylene polymers (B-1) and (B-2) were used. (B-1) Random polypropylene (manufactured by Prime Polymer Co., Ltd., product name Prime Polypro F227, MFR (230°C, 2.16 kg load): 7g / 10 min, melting point: 150°C, mmmm fraction: 96%) (B-2) Random polypropylene (manufactured by Prime Polymer Co., Ltd., product name Prime Polypro F327, MFR (230°C, 2.16 kg load): 7g / 10 min, melting point: 140°C, mmmm fraction: 95%)

[0089] [Ethylene-based polymer (C)] As the ethylene polymer (C), a high-pressure low-density polyethylene (manufactured by Mitsui Dow Polychemicals, trade name Mirason 11P, MFR (190°C, 2.16 kg load) 7.2 g / 10 min, density: 0.917 g / cm 3 ) (C1-1), ethylene-propylene copolymer (MFR (190°C, 2.16 kg load): 0.6 g / 10 min, density: 0.869 g / cm 3 ) (C2-1) was used.

[0090] The physical properties of 1-butene-ethylene copolymer (A) were measured by the following methods. The physical properties are shown in Table 1. a) Composition ratio, B value and isotactic triad fraction (mm fraction) The composition ratio, B value and isotactic triad fraction (mm fraction) are 13 It was determined by analysis of C-NMR spectrum, specifically, by the method described in JP 2007-186664 A. In this specification, the content of structural units derived from propylene is also referred to as the "C3 content" or "propylene content," the content of structural units derived from ethylene is also referred to as the "C2 content" or "ethylene content," and the content of structural units derived from 1-butene is also referred to as the "C4 content."

[0091] b) MFR The MFR was measured at 230°C and a load of 2.16 kg in accordance with ASTM D1238.

[0092] c) Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) As the GPC device, a Waters gel permeation chromatograph Alliance GPC-2000 was used, and polystyrene-equivalent Mw and Mn were measured under the following conditions, and Mw / Mn was calculated. Separation columns: 2 TSKgel GNH6-HT columns manufactured by Tosoh Corporation, and 2 TSKgel GNH6-HTL columns manufactured by Tosoh Corporation (both columns have a diameter of 7.5 mm and a length of 300 mm) Column temperature: 140℃ Mobile phase: o-dichlorobenzene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) containing 0.025 wt% BHT (manufactured by Takeda Pharmaceutical Co., Ltd.) as an antioxidant. Travel speed: 1.0mL / min Sample concentration: 15mg / 10mL Sample injection volume: 500 μL Detector: Differential refractometer Standard polystyrene: molecular weight Mw<1000 and Mw>4×10 6 In this case, use a product manufactured by Tosoh Corporation, and the molecular weight is 1000≦Mw≦4×10 6 In this case, use Pressure Chemical Co.

[0093] d) Elution peak temperature, peak area, and amount of components eluted at -20°C Using a high-throughput composition distribution analyzer, CEF, manufactured by Polymer Char, the temperature at the apex of the elution peak was taken as the elution peak temperature under the following conditions, and the peak area was calculated from the integrated value of the peak, and the proportion of the component eluted at -20°C was calculated as the amount of the component eluted at -20°C. Equipment: High-throughput composition distribution analyzer, CEF (PolymerChar) Detector (built-in): IR5 type infrared spectrophotometer (PolymerChar) Detection wavelength: Concentration sensor CH2 νa 3.42μm (2,920cm -1 ) Methyl sensor CH3 νa 3.38μm(2,960cm -1 ); Column: CEF column (Polymer Char), length 150 mm, capacity 2.2 mL Mobile phase: o-dichlorobenzene (ODCB), with BHT Sample concentration: 16mg / 8mL Dissolution conditions: 150℃, 60min (in N2 atmosphere) Injection volume: 0.2mL Temperature lowering conditions: 95℃→-20℃: 0.5℃ / min, flow rate 0.0 mL / min Temperature rise conditions: -20℃→140℃: 1.0℃ / min, flow rate 0.5 mL / min

[0094] e) Melting point, heat of fusion Using a hydraulic hot press molding machine set at 190°C, the material was heated for 5 minutes, molded for 2 minutes under a pressure of 10 MPa, and then cooled for 4 minutes at 20°C under a pressure of 10 MPa to produce a 0.5 mm thick sheet (test piece). After molding, a test piece weighing about 10 mg was left at room temperature for 72 hours and then cooled to -100°C at 10°C / min in a nitrogen atmosphere (20 mL / min). Next, the test piece was held at -100°C for 5 minutes and then heated to 200°C at 10°C / min. The temperature at the peak of the crystal melting peak was taken as the melting point, and the heat of fusion was calculated from the integrated value of the peak.

[0095] [Table 1]

[0096] In the following Examples and Comparative Examples, the physical properties of the sealant resin compositions and films were measured or evaluated by the following methods. The evaluation results are shown in Table 2 below.

[0097] [Whitening resistance test] Using a single screw extruder of φ40 mm, the polymers were melt-kneaded in the ratios (parts by mass) shown in Table 1 at a melt temperature of 210°C and a rotation speed of 40 to 50 rpm to produce pellets. The sealant resin composition (X) was heated for 5 minutes using a hydraulic hot press molding machine set at 190°C, molded for 2 minutes under a pressure of 10 MPa, and then cooled for 4 minutes at 20°C under a pressure of 10 MPa to produce a 0.5 mm thick sheet (test piece). A No. 2 dumbbell as specified in JIS K 6251 was made from the sheet, and the hue before stretching (L value (before stretching)) and the hue when stretched 15 mm at a pulling speed of 50 mm / min (L value (after stretching)) were measured using a spectrophotometer (CM-3700d, manufactured by Konica Minolta, Inc.), and the hue change (ΔL) was calculated based on the following formula. A smaller ΔL value indicates better whitening resistance. Evaluation criteria for whitening resistance ΔL = L value (after stretching) - L value (before stretching) ○: ΔL≦15 ×:ΔL≧16

[0098] [Laminate properties] The polymers shown in Table 2 were kneaded in the ratios (parts by mass) shown in Table 2 using an extruder (φ40 mm), and the resulting pellets were extruded at 230°C using a cast film molding machine to produce single-layer unstretched films with thicknesses of 50 and 100 μm. Next, a 25 μm-thick stretched PET film (manufactured by Toray) was laminated on the substrate layer surface of the resulting unstretched film via an adhesive layer by dry lamination to produce a laminate. The following evaluations were carried out using this laminate.

[0099] <Heat seal (HS) strength (before heat treatment)> A test specimen was prepared by stacking, in this order, a 50 μm thick Teflon (registered trademark) sheet, two of the obtained laminated films, and another 50 μm thick Teflon (registered trademark) sheet.

[0100] The heat seal bar of a heat seal tester (manufactured by Tester Sangyo Co., Ltd., TB-701B type) was set to a width of 15 mm and a length of 300 mm, the temperature of the lower side of the seal bar was set to 70°C, and the temperature of the upper side of the seal bar was set to 190°C, and the test body was sandwiched between the seal bars and heat sealed for 1.0 second at a pressure of 0.2 MPa. Thereafter, the two Teflon (registered trademark) sheets were removed to obtain a laminated film, which was left at 23°C for one day. A 15 mm wide slit was made in the laminated film so as to include the heat-sealed portion, and the non-heat-sealed portion was chucked to a tensile tester (manufactured by Intesco Co., Ltd., IM-20ST). The maximum load was measured when the heat-sealed portion was peeled off in the direction of 180° at a speed of 300 mm / min. This measurement was performed five times, and the average value of the maximum load was taken as the heat seal strength.

[0101] <Heat seal (HS) strength (after heat treatment)> In the test for HS strength (before heat treatment), the heat seal strength after heat treatment was measured in the same manner as in the test for HS strength (before heat treatment), except that instead of the two sheets of the monolayer unstretched film, two sheets of the monolayer unstretched film obtained above were used which had been heat-treated at 85°C for 5 days.

[0102] <Heat seal (HS) strength retention rate> The HS strength retention was calculated from the HS strength before and after the heat treatment using the following formula. The larger this value, the better the heat resistance. Based on the HS strength retention, the HS strength retention was evaluated according to the following criteria. HS strength retention rate (%) = 100 × HS strength (after heat treatment) / HS strength (before heat treatment) ·Evaluation criteria for HS strength retention ○: HS strength retention is 80% or more ×: HS strength retention rate is less than 80%

[0103] Appearance evaluation after heat treatment The monolayer unstretched film was heat-treated at 85° C. for 5 days, and the presence or absence of change in the appearance of the film surface was evaluated before and after the treatment. ○: No change in appearance ×: Bleeding occurred over the entire surface (the entire surface was sticky)

[0104] [Example 1] The above propylene-ethylene or α-olefin copolymer (A) was used in an amount of 20 parts by mass of the above propylene-ethylene copolymer (A1-1), and the above propylene-based polymer (B) was used in an amount of 80 parts by mass of the above (B-1), to obtain a sealant resin composition by the above method, and then each physical property was measured or evaluated by the above method. The results are shown in Table 2.

[0105] [Examples 2 to 8, Comparative Examples 1 to 7] A sealant resin composition was obtained in the same manner as in Example 1, except that instead of the propylene-ethylene copolymer (A1-1) and the propylene-based polymer (B-1) in Example 1, the resin components shown in Table 2 were used in the amounts shown in Table 2, and then the physical properties were measured or evaluated. The results are shown in Table 2.

[0106] [Table 2]

Claims

1. A propylene / α-olefin copolymer (A) that satisfies the following requirements (a1) to (a4); A propylene-based polymer (B) that satisfies the following requirements (b1) and (b2); The sealant resin composition (X) contains: (a1): When the total of the structural unit (i) derived from propylene and the structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms excluding propylene is taken as 100 mol %, the content of the structural unit (i) is 51 to 95 mol %, and the content of the structural unit (ii) is 5 to 49 mol %. (a2): In crystallization elution fractional chromatography measurement, the elution peak is at 10 to 55° C. (a3): In a crystallization elution fractionation chromatography measurement, the ratio of components eluted at -20°C or lower is 80 mass% or less. (a4): The melting point measured by a differential scanning calorimeter is 50 to 100°C. (b1): The melting point measured by a differential scanning calorimeter is 110 to 170°C. (b2): The isotactic pentad fraction is 90% or more.

2. The propylene / α-olefin copolymer (A) is Propylene-ethylene copolymer (A1), Propylene / 1-butene copolymer (A2), Propylene / 1-octene copolymer (A3), and Propylene-ethylene-1-butene copolymer (A4) The sealant resin composition (X) according to claim 1, which consists of one or more selected from the group consisting of:

3. The sealant resin composition (X) according to claim 1, further comprising an ethylene-based polymer (C).

4. The sealant resin composition (X) according to claim 1, comprising 1 to 50 mass% of the propylene-α-olefin copolymer (A), 30 to 99 mass% of the propylene-based polymer (B), and 0 to 20 mass% of the ethylene-based polymer (C) (wherein the total of the propylene-α-olefin copolymer (A), the propylene-based polymer (B), and the ethylene-based polymer (C) is 100 mass%).

5. A sealant film comprising at least one layer comprising the sealant resin composition (X) according to claim 1.

6. A laminate comprising a sealant layer containing the sealant resin composition (X) according to claim 1 and a base layer, wherein the base layer is at least one base film selected from the group consisting of polyolefin films, polystyrene films, polyester films, polyamide films, laminated films of polyolefins and gas barrier resin films, metal foils, paper, and vapor-deposited films.

7. The laminate according to claim 6 , wherein the sealant layer and the base layer are bonded together by any one of a melt extrusion lamination method, a thermal lamination method, and a dry lamination method.

8. The laminate according to claim 6, wherein the substrate film is an aluminum foil.

9. A package comprising the laminate according to any one of claims 6 to 8.

10. A lithium ion battery comprising the packaging of claim 9.

11. An electricity storage device comprising the sealant film according to claim 5 .

Citation Information

Patent Citations

  • Resin composition for sealant film, and sealant film

    JP1999221884A

  • Sealant film

    JP2020114908A